2021
DOI: 10.3390/v13102048
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Canine RIG-I against Canine Influenza Virus and Interactions between Canine RIG-I and CIV

Abstract: RIG-I functions as a virus sensor that induces a cellular antiviral response. Although it has been investigated in other species, there have been no further studies to date on canine RIG-I against canine influenza virus (CIV). In the present study, we cloned the RIG-I gene of beagle dogs and characterized its expression, subcellular localization, antiviral response, and interactions with CIV proteins. RIG-I was highly expressed and mainly localized in the cytoplasm, with low levels detected in the nucleus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…However, we still know relatively little about cellular autophagy serving for RIG-I regulation. To investigate whether cellular autophagy was involved in the phenomenon in Figure 1, we detected the expression level of LC3B protein in MDCK cells protein samples with the same treatments as our previous study [18]. The overexpression of RIG-I against H3N2 CIV experiments showed that the ratio of LC3B-II/GAPDH was relatively higher when the Flag-RIG-I plasmid dose for transfection was more than 2500 ng (Figure 2A,B).…”
Section: Cellular Autophagy Is Essential To the Regulation Of Excessi...mentioning
confidence: 73%
See 3 more Smart Citations
“…However, we still know relatively little about cellular autophagy serving for RIG-I regulation. To investigate whether cellular autophagy was involved in the phenomenon in Figure 1, we detected the expression level of LC3B protein in MDCK cells protein samples with the same treatments as our previous study [18]. The overexpression of RIG-I against H3N2 CIV experiments showed that the ratio of LC3B-II/GAPDH was relatively higher when the Flag-RIG-I plasmid dose for transfection was more than 2500 ng (Figure 2A,B).…”
Section: Cellular Autophagy Is Essential To the Regulation Of Excessi...mentioning
confidence: 73%
“…Our previous study identified the antiviral effect of canine RIG-I against canine influenza virus (CIV), whereby overexpression of canine RIG-I could strongly suppress the CIV replication in MDCK and HEK 293T cells [18]. However, we found that more than 2500 ng canine RIG-I overexpression reduced the antiviral effect against CIV.…”
Section: Excessive Expression Of Canine Rig-i Triggered Unknown Negat...mentioning
confidence: 83%
See 2 more Smart Citations
“…For the influenza virus, Retinoic acid-inducible gene I (RIG-I, encoded by the DDX58 gene) is the major pathogen recognition receptor (PRR) of the cytoplasm to induce the production of type I interferon (IFN-α/β) and pro-inflammatory cytokines [ 19 ]. It has been reported that canine RIG-I suppresses the replication of the canine influenza virus (CIV) in adherent MDCK (aMDCK) cells [ 20 ]. The secreted IFN-α/β activates the JAK/STAT signaling pathway, leading to the induction of hundreds of IFN-stimulated genes (ISGs) including ISG15, MX1, PKR, OAS1, IFI44, and IFITM3 [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%